Quality of life in minor siblings of childhood leukemia survivors, long‐term after diagnosis: A LEA study (for Leucemies de l'Enfant et de l'Adolescent—childhood and adolescent leukemia). Issue 6 (28th October 2014) - Berbis, Julie; Oudin, Claire; Alessandrini, Marine; Vercasson, Camille; Barlogis, Vincent; Chambost, Hervé; Michel, Gérard; Auquier, Pascal
Abstract Objective The objectives of this study are to assess the quality of life (QoL) of siblings of childhood leukemia survivors in comparison with population controls and to identify determinants of sibling's QoL. Methods The nearest‐aged siblings (8–17 years) of minor CLS participating in the French LEA cohort (Childhood and Adolescent Leukemia), at the Marseilles center, were included. Siblings' QoL was self‐reported using the 'Vécu et Santé Perçue de l'Adolescent et l'enfant' questionnaire. Results were compared with those obtained for age‐matched and sex‐matched French controls subjects. Characteristics likely to be associated with siblings' QoL (sibling's and survivor's sociodemographic and health‐related and cancer‐related characteristics) were explored through multivariate analysis. Results Fifty‐one siblings participated (mean age 12.7 ± 2.8 years, mean follow‐up duration from diagnosis to evaluation 8.8 ± 2.5 years). They reported a significantly higher perception of QoL compared with the general population regarding psychological domains, while reporting a lower perception regarding social domains. In multivariate analysis, older age at diagnosis for both siblings and survivors was risk factor for impaired psychological QoL. An elevated leukemia burden index was linked with lower scores in self‐esteem dimension, whereas having at least one sequelae for the survivor was linked with better scores in psychological well‐being dimension. Low or middle affluence and older sibling's age at diagnosis were risk factors for impaired social QoL. Maximal R2 was 30%. Conclusions Minor siblings of CLS reported a relatively good QoL, particularly in psychological domains. Given the low proportion of QoL variability explained, other contributing factors (e.g., family functioning) must be explored. Copyright © 2014 John Wiley & Sons, Ltd.